Analysis of buried gate MESFET under dark and illumination - Verma M.K.; Pal B.B. (My University, 2025)
D.C. analysis has been carried out for a buried-gate GaAs metal semiconductor field effect transistor (MESFET) under dark and front illumination. The photovoltage I-V characteristics and the transconductance of the device have been evaluated. The results indicate very good performance of the device compared to other devices like MESFET under back illumination and MESFET with front illumination having surface gate. Thus, buried-gate optical field effect transistor (OPFET) will be highly suitable for optical communication and optical computing.